ZAK TRANSFORM - Nuñez Ramirez, Luis Miguel (2011)
The Zak transforrn is a technique tha tplays an important role in studying theproblem of Gabor representation in signal analysis. Tlie Zak transform of a signal f can beconsidered as a generalization of the discrete Fourier transforrn, we study some properties and its application in demonstrating the Balian-Low theorem which is a fundamental resultin the analysis time-frequency,